Biology Education: The Value of Taking Student Concerns Seriously - Michael J. Reiss (MDPI AG, 2018)
This article examines the question of how biology courses can take student concerns more seriously than they often do. The focus is on school biology although the arguments apply to other biology courses too. The article begins by examining Michael Young's argument that schools should provide students with access to powerful knowledge-the sort of knowledge that they are unlikely to obtain from elsewhere-and compares this with John White's argument that the curriculum should enable student flourishing, and that as part of this, there should be more student choice about what they study. It then discusses recent work on the benefits of independent research projects, in which students undertake authentic investigative work where they have considerable control over the work, and concludes that these generally motivate students and are a good source of learning for them. It goes on to examine what lessons might be learnt for school biology from the informal learning sector, such as Natural History Museums, where visitors have great autonomy with regard to what they study. Finally, it looks at the concept of 'worldviews' and argues that this provides another argument for taking student concerns seriously. The article concludes that taking student concerns seriously in school biology would facilitate human development, in particular, development towards greater student autonomy, and that this can be done in ways that have been tried and allow for high quality biology teaching and learning.